Perceptions and experiences of diploma nursing students on clinical learning. A descriptive qualitative study in Tanzania - Angela Jacob; Saada Seif; Yuda Munyaw (BMC, 2023)
Abstract Background The quality of nursing education depends largely on the experience student receive in the clinical environment. The learning environment is complex with factors that may positively or negatively influence students learning. The current study aimed to explore the experiences and perceptions of diploma nursing students toward their clinical learning in Dodoma-Tanzania. Methods A qualitative descriptive study design was employed. The study was conducted in four nursing schools involving 32 nursing students who were purposively selected. Data was collected using focus-group discussions and analyzed using thematic analysis. Results Three main themes emerged during the discussions: experience on personal and technical support for clinical learning, the importance of the clinical environment in clinical learning, and insufficient clinical educational planning. The majority of students had negative experiences including poor clinical supervision, lack of equipment, congestion of students, and inability to meet clinical objectives. Few students had positive experiences related to exposure to a real clinical environment and great support from staff nurses. Conclusion Students had mixed experiences, both positive and negative on their clinical learning. The majority of students had negative experiences. This may have a serious impact on the student completing their education, the services they will offer to patients when employed, and nursing professional development.